IMPLEMENTASI PENILAIAN HASIL BELAJAR BAHASA INGGRIS KURIKULUM 2013 BERDASARKAN PERMENDIKBUD NOMOR 53 TAHUN 2015 DI SMPN 1 PAMEKASAN - Siti Azizah (Research Institute and Community Engagement of IAIN MADURA, 2018)
The result of Monitoring and Evaluation on the implementation of 2013 curriculum in the level of Junior High School in the year of 2014 showed that one of the teachers’ difficulties in implementing the 2013 curriculum is the implementing Evaluation. Related to this problem, the government has done many revisions on the Evaluation part, the last revision done by the Educational and Cultural Department is the emergence of the Provision of the Educational and Cultural Department No.53 year 2015. The provisions in the Educational and Cultural Department is started to be implemented in the Even Semester year academic 2015/ 2016 in all educational levels which implement the 2013 curriculum, including the State Junior High School 1 (SMPN 1) Pamekasan. Therefore, the researcher is interested to know how far the implementation of the English Evaluation of 2013 curriculum in SMPN 1 Pamekasan based on the constitution of Educational and Cultural Department No.53 year 2015. The result of this research is, first the implementation of English Evaluation based on the Constitution of Educational and Cultural Department No.53 year 2015 has not been done correctly. Second, the teachers found some difficulties in evaluating the students’ English work based on the Constitution of Educational and Cultural Department No.53 year 2015, they are 1) many indicators in behavioral evaluation that needs to be analyzed deeper, they are being polite, discipline, self confidence, and cooperation, 2) in formulating the grid of skill aspect, especially in formulating the evaluation suitable with the skill that is needed to be evaluated, 3) in the project evaluation technique and portfolio evaluation technique.